Feasibility of using dried blood spots for HIV viral load testing among HIV-infected individuals in Thailand using QIAGEN QIAsymphony-artus HIV-1 platform - Viraporn Thepbundit (2019)
© 2019 Wiley Periodicals, Inc. In settings where plasma preparation and sample centralization are not feasible or inconvenient, dried blood spots (DBS) could be used as an alternative specimen to plasma to assess antiretroviral treatment response among HIV-infected individuals. This study was aimed to (1) validate the recent QIAsymphony-artus assay for DBS HIV viral load (VL) and (2) assess the feasibility of measuring HIV VL on DBS using this assay in Thailand. Ethylenediaminetetraacetic acid-blood samples from 99 HIV-infected individuals were used to prepare paired DBS and plasma. Also, DBS samples were shipped to three distant hospitals in the northern region. After short-term storage, DBS were returned by regular post to the AMS laboratory and were re-tested for HIV VL using the same platform. HIV VL results were compared using Pearson's correlation and Bland-Altman analysis. DBS HIV VL fairly correlated to plasma HIV VL (R = 0.62) with a mean difference of 0.02 log10IU/mL (SD = 1.06). A high correlation (R = 0.79) was observed between HIV VL in DBS before and after shipping (mean difference = 0.14 log10IU/mL, SD = 0.74), indicating good stability of HIV RNA in DBS. DBS can be used as an alternative specimen for HIV VL monitoring in Thailand. However, measurement of HIV VL with the QIAGEN QIAsymphony-artus assay should be improved, especially the DBS pre-extraction process.